POTENSI MANUSIA UNTUK BELAJAR MENGAJAR (Qalbu, Akal, Indra, Berfikir, Dan Motivasi) - Mardinal Tarigan (Universitas Islam Negeri Sumatera Utara Medan, 2022)
AbstractIndeed, Allah has created humans with the best of creation, Allah has given privileges to humans in the form of giving potential or abilities for each individual including the potential of the heart, mind, five senses, potential for thinking and motivation that makes human position higher than other creatures. It is also very useful for humans in the teaching and learning process so that they can understand the gifts given by God, namely the creation of the earth, oceans and nature in which they are to be taken advantage of for humans. the task of humans is to develop the abilities that exist within themselves and take advantage of the gifts that have been given as a way to increase piety to Allah. The objectives to be achieved in this research are to understand and know the existence of human potential, as well as knowing various types of basic human potential that are useful in educating individuals so that their potential development can run optimally. This research is a type of library research, so the data obtained are sourced from the literature. Collecting data by studying, exploring and quoting theories and concepts from a number of literatures, both books, journals, magazines, newspapers or other written works that are relevant to the research topic. The results showed that each individual has the potential in the form of heart potential, mind potential, human sense potential, thinking potential and motivation potential. The role of education and the teaching and learning process in the effort to develop human potential as students and educators is very necessary so that the development of their potential can run optimally.